Secuencia de meteorización y su relación con las propiedades de carga y superficie de la fracción arcilla de algunos andosoles de Costa Rica - González M, S.P.; Kozen, I.; Besoain M., E. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Mineralogical composition, TSS, CEC and charge density of the clay fraction of Costa Rican sediments and andosols were determined. The sampling was made following a toposequence from Mt Irazu (3400 m) to Meseta Central (1000 m). It is presumed that this parent material weathered according with to the following sequence: Volcanic ashes → amorphous gels of silica alumina, hydrated glasses, etc → allophane (B, AB, A) → metahalloysite. This sequence developed in an “horizontal” sense, from Irazu volcano to Meseta Central, increasing its age and the intensity of climatic conditions. The same sequence developed too in a “vertical” sense within the profiles, in these depositions, the oldest layer is the deeper one. For this research, the ashes from Irazu volcano are considered to be at time zero. Analytical records suggest the existence of bissingerite; its origin could be parallel to that of allophane. More research should be required to evidence its real existence and its formation. Values of TSS and CEC show a parallel variation with the evolution of clay minerals, i.e. values increase from rough ashes to allophane. A and then, decrease with the formation of metahalloysite. Charge density values, however, tend to stay constant at fixed pH-value, without influence of the mineralogical stage of the sampler. The use of TSS and CEC as a supplement of routine mineralogical analysis is helpful, because they show a trend according with clay evolution and differences in clays of similar constitution. This allows a better interpretation of the mineralogical analysis. CEC and charge density values were useful in order to identify the formation of highly unstable complexes with high content of free hydroxiles groups during the allophane synthesis.